The Implementation of Gamification Methods in the Edusting Application as an Educational Medium to Enhance Mothers Knowledge of Stunting - Deta, Bernadete; Wato, Robertus Resi (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Interventions for stunting are an urgent public health priority. Because mothers' limited knowledge about stunting has a direct impact on stunting prevention and management. One of the extraordinary outreach programs is the stunting socialization program for mothers of toddlers carried out at the integrated health post. However, the socialization action is considered too limited. Gamification is one potential approach to increase the effectiveness of these efforts by introducing game design and game elements into educational content in three areas: childcare practices, nutritional intake, and stunting prevention. This is expected to explore mothers' involvement and motivation to prevent stunting. Mothers certainly prefer a more attractive interactive interface and gamification applications will stimulate cognitive and emotional involvement so that mothers feel more comfortable in the learning process about stunting management. In this study, we present the design of an education that aims to help mothers understand and overcome stunting. This application is expected to make mothers better understand parenting patterns, nutrition, and stunting management so that it can help mothers' learning to increase the speed of mothers' understanding of stunting prevention.